Analisis Implementasi Peraturan Daerah Nomor 11 Tahun 2000 Tentang Pengaturan dan Pembinaan PKL Di Kota Semarang - Iqbal Hanafi; Budi Setiyono (Journal of Politic and Government Studies, 2017)
ABSTRACT             Street Traders are traders in an attempt to use the facilities and equipment that is easy or overhauled / transferred and or using businesses that occupy land owned by the local government or other parties. The increasing number of street vendors in the city, causing a variety of problems such as hygiene, safety and comfort. As a solution to these problems and to regulate street vendors, Semarang city government issued a Local Regulation No. 11 Year 2000 on Regulation and Development of street vendors.            The method used is a qualitative approach to data collection techniques are observation, interviews and document research. Informants in this study is the Head of the Office of Market Street Traders Semarang, Head of Operational Infrastructures, Head of Licensing Guidance and Counseling, Head of Planning and Control Division street vendors as well as some of the street vendors in the city of Semarang.            The results showed that after 15 years of the Regulation is implemented, have not been able to achieve the original purpose of which is expected towards the realization of Street Vendors of regular and orderly. There are still a lot of vendors who do not know this law and violates the contents of the legislation, there are several obstacles in its implementation or inhibiting factors either from the government or from the vendors themselves.            The recommendations can be given to the government is doing a consultation or meeting with street vendors in the city, held a training regularly for street vendors, improve the supervision and control of the street vendors so that fraud and violations of the law can be overcome and immediately followed up with more quickly.Keywords: Street Traders, Policy, Implementation